2021
DOI: 10.1080/09638288.2021.1971308
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between scoliosis, windswept hips and contractures with pain and asymmetries in sitting and supine in 2450 children with cerebral palsy

Abstract: Purpose: This cross-sectional study of 2450 children with cerebral palsy aimed to analyse the prevalence and association of scoliosis, windswept hips, hip and knee contractures. Methods: Logistic regression was used to estimate associations with pain, postural asymmetries, and ability to change position for children at Gross Motor Function Classification System (GMFCS) levels I-V, aged 0-18 years. Results: Most children with a deformity or contracture had postural asymmetries in both sitting and supine positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Our results indicate that a reduced ability to change and maintain a position increases the likelihood of an asymmetric posture. As noted above, asymmetric postures in sitting and lying are associated with scoliosis and windswept deformity in both children and adults with cerebral palsy ( 5 , 8 , 25 ), which might be explained by the longer time spent in these two positions. Several adults without asymmetries used adjustable beds and positioning equipment in lying.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our results indicate that a reduced ability to change and maintain a position increases the likelihood of an asymmetric posture. As noted above, asymmetric postures in sitting and lying are associated with scoliosis and windswept deformity in both children and adults with cerebral palsy ( 5 , 8 , 25 ), which might be explained by the longer time spent in these two positions. Several adults without asymmetries used adjustable beds and positioning equipment in lying.…”
Section: Discussionmentioning
confidence: 91%
“…Postural asymmetries are frequent and associated with a limited range of joint motion and an inability to change position (4,5). Asymmetric postures sustained for long periods of time are associated with deformities, contractures and pain, which most commonly affect the spine and the lower extremities (5)(6)(7)(8). Inability to move and having a sustained posture increases the likelihood for contractures, making each posture relative to the time spent in that position clinically important throughout a 24-h cycle (4,5,9).…”
Section: Introductionmentioning
confidence: 99%
“…For GMFCS levels IV and V, prevention of contractures at the hips, knees, and ankles is important for goals such as maintaining ability to assist with standing transfers, 100 allowing continued weight bearing for BMD, 67 and reducing asymmetries in lying and sitting positions that are associated with pain, windswept hips, and scoliosis. 101 Low levels of evidence support the use of night-time positioning to prevent contractures and windswept deformity. 102 However, supported-standing programmes may potentially be more effective because, in addition to promoting alignment, 65 they also promote weight bearing and active muscle contraction.…”
Section: Range Of Motionmentioning
confidence: 99%
“…Research has shown the impact of poor posture on quality of sleep. 16 Chronic sleep disruption can have an impact on cognitive functioning, mood and fatigue (Reynolds et al, 2010). 8 Reported improved sleep quality following provision of a sleep system.…”
Section: Introductionmentioning
confidence: 99%
“…2,7,15 Children with CP commonly experience poor posture and resulting secondary complications including pain and sleep disturbance at night, the likelihood of which increases with age and higher GMFCS levels. 7,16 There have been fewer studies investigating quality of life 8,10,11 and outcomes for carers. 7,8 Following a systematic review 6 recommendations were made for further research to establish benefits, including pain, posture and sleep quality and the impact on users and carers.…”
Section: Introductionmentioning
confidence: 99%